Pengaruh Konsentrasi Kombinasi Lactococcus Lactis Dengan Saccharomyces Cerevisiae Dan Lama Waktu Fermentasi Terhadap Kadar Karbohidrat Dan Kadar Abu Tepung Telur Itik - Kartika, Intan; Pratama, Andry; Utama, Dicky Tri (Jurnal Teknologi Hasil Peternakan, 2023)
Duck egg flour is one of the products processed from whole eggs through the drying process. The process of making egg flour can affect the quality of the flour produced. One way to maintain the quality of egg flour is by fermenting it before drying. The purpose of egg fermentation using Lactococcus lactis and Saccharomyces cerevisiae is to avoid browning caused by Maillard reactions and improve the quality of duck egg flour. This study aims to determine the effect of the concentration level of L. lactis and fermentation time on the carbohydrate content and ash content of duck egg flour. The research was conducted experimentally using a Complete Randomized Design Nested Pattern with fermentation times of 12 and 24 hours within L. lactis concentrations of 4%, 6%, and 8% with 24 replications. The research data obtained was analyzed using Analysis of Variance. The results showed that duck egg flour fermented in a 6% (b/v) L. lactis concentration for 12 hours produced 0.065% carbohydrate content and 4.52% ash content